2000
DOI: 10.1007/s004170000194
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of iris pigment epithelium into the choroid slows down the degeneration of photoreceptors in the RCS rat

Abstract: Transplantation of IPE cells slows down degeneration of the photoreceptors in the RCS rat. This photoreceptor-sparing effect by the IPE cells was observed even when the transplants were predominantly located within the choroid. The beneficial effect observed may be related to trophic factors possibly secreted by the transplanted IPE cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In contrast to similar studies by our group demonstrating rescue effects after transplantation of embryonic stem cells or iris pigment epithelial (IPE) cells in Royal College of Surgeons (RCS) rats, where the primary defect tends to be associated with the RPE cells [29][30][31] (our own unpublished data), the data presented here are most interesting, as in RP, as well as in the rho -/-mouse, the defect is situated in the photoreceptor cells themselves.…”
Section: Discussionmentioning
confidence: 68%
“…In contrast to similar studies by our group demonstrating rescue effects after transplantation of embryonic stem cells or iris pigment epithelial (IPE) cells in Royal College of Surgeons (RCS) rats, where the primary defect tends to be associated with the RPE cells [29][30][31] (our own unpublished data), the data presented here are most interesting, as in RP, as well as in the rho -/-mouse, the defect is situated in the photoreceptor cells themselves.…”
Section: Discussionmentioning
confidence: 68%
“…They have also demonstrated that in the short term photoreceptor rescue does not differ significantly from that after sham operation, but in long-term investigations there was clearly significant rescue potential of the IPE cell [21,22]. This, in turn, confirmed the hypothesis that the IPE cell is capable of influencing and possibly remodelling its environment by secreting cytokines and/or neurotrophic factors.…”
Section: Discussionmentioning
confidence: 85%
“…99 Despite the lack of visual improvement, subretinal IPE transplantation in patients with AMD may prevent recurrence of subretinal neovascularization. 35,68 We observed major differences in the gene expression profiles of primary RPE vs IPE harvested from the same donor eyes, including the lack of expression in IPE of genes known to be critical for RPE function. For example, IPE does not express the gene for retinol dehydrogenase, whose gene product is necessary for recycling visual pigments.…”
Section: Commentmentioning
confidence: 86%
“…67 Previous authors have concluded that IPE can survive at least 6 months after subretinal transplantation, but proper interpretation of these results is confounded by difficulty in identifying transplanted cells unequivocally. 65,66,73,86,87 Results of initial studies 68,88 suggested that subretinal or choroidal IPE transplantation may slow the rate of photoreceptor degeneration in the Royal College of Surgeons rat model for several months compared with untreated controls. However, the rescue effect of transplanted IPE cells was no better than that of sham surgery.…”
Section: Commentmentioning
confidence: 99%